2020
DOI: 10.1029/2019jb018700
|View full text |Cite
|
Sign up to set email alerts
|

Petrofabrics and Seismic Properties of Himalayan Amphibolites: Implications for a Thick Anisotropic Deep Crust Beneath Southern Tibet

Abstract: The bulk composition of overthickened Tibetan deep crust has been generally believed to be mafic granulite with eclogite at the lowermost crust. However, a granulitic/eclogitic deep crust is in contradiction to geological and geophysical observations in southern Tibet. Here we present petrofabrics and seismic properties of amphibolites from exhumed crustal part of the Indian plate in the eastern Himalayan syntaxis. Our results show strong fabrics of amphibole, nearly random fabrics of plagioclase and strong se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…Model CPOs were used further to explore the effect of amphibole CPOs on seismic anisotropy. CPOs were modeled using the Bingham Distribution of Quaternions, which can represent the ideal CPO types in amphibole (type I, type III and type IV) based on the relationship among the shape parameters (λ 1 , λ 2 , λ 3 , λ 4 ) (Kunze & Schaeben, 2005; Biedermanna et al., 2018; Li et al., 2020). It can also represent the transitional cases from type I to type III and type I to type IV.…”
Section: Discussionmentioning
confidence: 99%
“…Model CPOs were used further to explore the effect of amphibole CPOs on seismic anisotropy. CPOs were modeled using the Bingham Distribution of Quaternions, which can represent the ideal CPO types in amphibole (type I, type III and type IV) based on the relationship among the shape parameters (λ 1 , λ 2 , λ 3 , λ 4 ) (Kunze & Schaeben, 2005; Biedermanna et al., 2018; Li et al., 2020). It can also represent the transitional cases from type I to type III and type I to type IV.…”
Section: Discussionmentioning
confidence: 99%
“…These studies propose that the observed crustal anisotropy mainly originates from CPOs formed during ductile deformation of the middle-lower crust (Agius and Lebedev, 2017;Chen et al, 2016;Shapiro et al, 2004). Amphibole, because of its abundance in the deep crust and high intrinsic seismic anisotropies, has often been proposed to explain strong crustal anisotropies (Ko and Jung, 2015;Li et al, 2020;Tatham et al, 2008). However, observations of naturally and experimentally deformed amphibolites show that most of the processes cited above may produce strong amphibole CPOs (Elyaszadeh et al, 2018;Getsinger and Hirth, 2014;Imon et al, 2004;Ko and Jung, 2015;Skrotzki, 1992;Stokes et al, 2012;Tommasi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In the Himalaya-Tibet orogenic belt, due to the differences in heat flow and heat production (Supplementary Fig. 5 ), the temperature at Moho discontinuity (~65 km) 48 , 49 reaches to 1340 K, and the lithospheric thickness is close to 150 km (Fig. 3b ).…”
Section: Resultsmentioning
confidence: 99%
“…( 8 )–( 10 ), the geotherm profiles are calculated from the surface downward using a depth increment of 10 m in each step (Δ z = 10 m). Following this approach, the crustal structures, composition, and heat production in the Sulu UHPM belt 50 , 51 and Himalaya-Tibet orogenic belt 48 , 49 , 52 , 84 , 85 are shown in Supplementary Fig. 5 , and the temperature profiles are given in Fig.…”
Section: Methodsmentioning
confidence: 99%